2014
DOI: 10.1590/0034-737x201461060012
|View full text |Cite
|
Sign up to set email alerts
|

Application of GA3 and girdling of branches on the production of extemporaneous fruits of 'Tahiti' acid lime

Abstract: Aplicação de GA 3 e anelamento de ramos na produção de frutos extemporâneos de limeiras ácidas 'Tahiti'Objetivou-se, neste trabalho, avaliar os efeitos do anelamento de ramos e da aplicação de GA 3 , ainda na florada da safra principal, sobre a formação de estruturas reprodutivas, o pegamento e a produção de frutos da florada subsequente, extemporânea, de limeira ácida 'Tahiti'. Utilizou-se o delineamento experimental em blocos casualizados, com cinco repetições, em esquema fatorial 4 x 3. O primeiro fator foi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…In most of the reviewed studies (Fig 8), exogenous GA applications during the induction period consistently reduced flower formation [85,87,89,90,97,98,106,102,107–111], while the application of Paclobutrazol (PBZ), a known antagonist of GA, increased the number of flowers [90,108]. As when temperature and water stress were manipulated for floral induction, GA also affected inflorescence type.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In most of the reviewed studies (Fig 8), exogenous GA applications during the induction period consistently reduced flower formation [85,87,89,90,97,98,106,102,107–111], while the application of Paclobutrazol (PBZ), a known antagonist of GA, increased the number of flowers [90,108]. As when temperature and water stress were manipulated for floral induction, GA also affected inflorescence type.…”
Section: Discussionmentioning
confidence: 99%
“…Most experiments were performed on young trees (Fig 5) under very controlled conditions and with repeated GA applications. GA applications were performed at any time during the induction period with good results, even on days before flowering [85,87,89,90,97,98,106,102,107–111]. It has been suggested that this technique can be used to mitigate alternate bearing in “on” years or to merely control the constant heavy flowering of some varieties [106,112].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the absence of statistical difference, a trend towards increased foliar concentration of carotenoids in plants with 100% girdling is evident. Accumulation of carbohydrates in the canopy may cause retroinhibition of photosynthesis, hinder CO 2 assimilation and cause oxidative stress (Pereira et al, 2014;Rivas et al, 2007). Under such circumstances, carotenoids take on photoprotective importance, as they remove the reactive species that cause oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Girdling prevents assimilation from being transported to the root system, increasing temporary retention of carbohydrates in the tree canopy and thus promoting greater fruit fixation (Santos et al, 2014). According to Pereira et al (2014), girdling increases the number and size of C. latifolia fruit. Despite the benefits of girdling, the incision into the stem may cause accumulation of phytoregulators and other metabolites, bringing undesired effects such as reduced plant size, lower photosynthesis rate, yellowing leaves and reduced root growth (Pereira et al, 2010(Pereira et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%